Role of skilled female construction worker (Mason) in post- earthquake reconstruction and their Socio-Economic changes: a case of Gorkha Earthquake, Nepal - Amatya, Sukirti (Brac University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2019.